2018
DOI: 10.1002/admi.201800616
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crack‐Activated Ultrasensitive Impedance Strain Sensor

Abstract: A development of single-crack-activated impedance strain sensors with unprecedented sensitivity is demonstrated first. The gauge factor of the device is beyond 10 8 in 10 −4 strain range in comparison with the reported highest gauge factor 1.5 × 10 5 within 6e-1 strain range, and the displacement sensitivity is 1.6 MΩ nm −1 . The extremely high sensitivity is attributed to the transition region which has never been studied before. Multiplecrack-based sensors, however, cannot work in the transition region due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
0
25
0
2
Order By: Relevance
“…The stain sensor made with multi-layer silver Schematic diagram of crack-based sensor based on PDMS. (a) One-step direct transfer preparation process of Ag Np-based tensile strain sensor on PDMS substrate [60] ; (b) molecular dynamics-based numerical simulation results of Ag-Np film stretching/relaxation process [60] ; (c) schematic diagram of the working principle of a single-crack-based strain sensor [1] ; (d) the template transfer method is used to fabricate the CBS [69] .…”
Section: Polydimethylsiloxane-based Crack Sensormentioning
confidence: 99%
See 3 more Smart Citations
“…The stain sensor made with multi-layer silver Schematic diagram of crack-based sensor based on PDMS. (a) One-step direct transfer preparation process of Ag Np-based tensile strain sensor on PDMS substrate [60] ; (b) molecular dynamics-based numerical simulation results of Ag-Np film stretching/relaxation process [60] ; (c) schematic diagram of the working principle of a single-crack-based strain sensor [1] ; (d) the template transfer method is used to fabricate the CBS [69] .…”
Section: Polydimethylsiloxane-based Crack Sensormentioning
confidence: 99%
“…The increased sensitivity due to the increased crack density also leads to the complexity of the process of processing the signal, and the sensor exhibits unstable performance. Ye et al reported a single-crack-activated ultra-sensitive crack-based strain sensor [1] . Within the strain range of 10 −4 , the gauge factor of the device is beyond 108.…”
Section: Polydimethylsiloxane-based Crack Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…carbon nanotubes, graphene), metal films, conductive polymers, and their hybrid micro/nanostructures. [8][9][10][11] Silver, including Ag nanowire, 12 nanoparticles, 13 inks, 14 and flakes, 15 has been the widest used metal materials in flexible electronics, due to its highest electronic conductivity of all metals, chemical stability higher than that of Cu, acceptable cost lower than that of Au. 16,17 For example, by mixing silver nanoparticles into rubber fibers, Park et al prepared a highly stretchable circuits through a fabrication process that can incorporate nozzle printing, inkjet printing, and spray printing to fabricate strain sensor.…”
mentioning
confidence: 99%